When Risk Meets Confidence: How ESG and Innovation Shape Corporate Finance in Emerging Markets - Husni, Tafdil; Rahim, Rida; Mardiani, Sari; Dwipananda, Rizki Fadhel (International Journal of Energy Economics and Policy, 2026)
This study investigates how macroeconomic uncertainties and firm-level behavioral and innovation factors interact to shape corporate financial outcomes in emerging markets. We specifically investigate the interaction between geopolitical risk (GPR), economic policy uncertainty (EPU), research and development (R&D) intensity, and managerial overconfidence on corporate leverage and stock returns, with environmental, social, and governance (ESG) performance serving as a moderating variable. Using panel data from listed firms across Indonesia, Malaysia, and Thailand during 2014–2024, the results reveal that GPR, R&D intensity, and managerial overconfidence increase leverage, whereas GPR reduces stock returns and EPU enhances them. R&D and managerial overconfidence do not significantly affect returns, and stock returns do not mediate the relationship between risk and leverage. Moreover, ESG performance amplifies the effects of GPR and EPU on both leverage and returns. By integrating macro-financial uncertainty, managerial behavior, and sustainability dimensions, this study contributes to the literature on corporate finance under uncertainty and provides policy-relevant insights for regulators and investors in emerging markets.